RACHID AL DAIF’S DEAR MR. KAWABATA: AN ALLEGORY OF THE RECONSTRUCTION OF POST-WAR BEIRUT - Daisy Waked (European Scientific Journal, ESJ, 2014)
The reconstruction of postwar Beirut projects the image of a modern city, oblivious of its past. Yet, the remnants of war are in constant struggle with this new identity of Beirut. Parallel to this dilemma, Rachid Al Daif’s narrator in Dear Mr. Kawabata witnesses a struggle between tradition and modernity. This article discusses the sources of both dilemmas and their manifestations: the narrator’s dilemma is an allegory of the reconstructed Beirut due to the driving forces that constitute their struggles. Amnesia and the ghost-like presence of memory are the two opposing forces that result in the schizophrenic identity of Beirut and in the narrator’s struggle. Both Beirut and the narrator experience a loss of memory at times and its haunting shadowy presence at others. Hence the inevitable need to explore the remnants of the memory of war to bring about the conscious awareness and acceptance of the past.